1995
DOI: 10.1089/scd.1.1995.4.149
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Proliferation Is Dependent on Human Serum and Markedly Increased Utilizing an Enriched Supplemented Basal Medium

Abstract: We studied the effects of basal medium and human serum on the ex vivo expansion of CD56+/CD3- natural killer cells (NK). We demonstrated that sorted NK cultured for 18 days with 10% human AB serum without accessory cells in a 2:1 DMEM/F12 basal medium expanded significantly greater (6.4 +/- 0.9-fold, n = 14) than when cultured in standard RPMI 1640 basal medium (3.7 +/- 0.67-fold, n = 16; p = 0.019). Supplementation of the DMEM/F12 mixture with 2-mercaptoethanol (2ME), ethanolamine, L-ascorbic acid, and sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…In a search for suitable conditions that would reproducibly generate high numbers of functional NK cells from early progenitor cells, we isolated CD34 + CD38 + cells from cord blood, bone marrow and mobilized PB and cultured them under different conditions combining cytokines and stromal cells. As previously reported [21], we found that a mixture of 10 % human serum and 5 % FCS was optimal for the proliferation and maturation of NK cells (data not shown). No significant proliferation was observed in the absence of SCF which was therefore systematically added.…”
Section: Cd34supporting
confidence: 80%
“…In a search for suitable conditions that would reproducibly generate high numbers of functional NK cells from early progenitor cells, we isolated CD34 + CD38 + cells from cord blood, bone marrow and mobilized PB and cultured them under different conditions combining cytokines and stromal cells. As previously reported [21], we found that a mixture of 10 % human serum and 5 % FCS was optimal for the proliferation and maturation of NK cells (data not shown). No significant proliferation was observed in the absence of SCF which was therefore systematically added.…”
Section: Cd34supporting
confidence: 80%
“…CD5-depleted leukocytes were cultured for 14 days (9 samples) or for 21-25 days (4 samples) days in media containing 60% DMEM, 30% HAMS F-12 + 2 mM L-glutamine, 10% heat-inactivated human serum, ß-mercaptoethanol ethanolamine, sodium selenite, and ascorbic acid, as described (Pierson et al, 1995). Samples for the 14 day culture were divided into 3 treatment groups, each containing 1,000 IU/mL of IL-2, 10 ng/mL of IL-15, or 1,000 IU/mL IL-2 + 10 ng/mL IL-15.…”
Section: Methodsmentioning
confidence: 99%
“…The DMEM/F12-based medium was developed to maximize NK cell growth 50 and is supplemented with 24 M 2-mercaptoethanol, 50 M ethanolamine, 20 mg/L ascorbic acid, 50 g/L sodium selenite (Na 2 SeO 3 ), 100 U/mL penicillin, and 100 U/mL streptomycin (Gibco). Twenty percent heat-inactivated human AB serum (North American Biologicals, Miami, FL) was used at culture initiation that was reduced to 10% for subsequent media changes.…”
Section: Culture Of Hematopoietic Progenitorsmentioning
confidence: 99%